The Comprehensive Systematic Review of Relationship between Education Level and Self-Management in Patients with Type 2 Diabetes Mellitus - Fifin Anisa (International Medical Journal Corp. Ltd, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) requires sustained self-management behaviors for optimal glycemic control and prevention of complications. While education level is frequently hypothesized to influence self-management capacity, evidence regarding this relationship remains inconsistent. Methods: A systematic review was conducted following PRISMA guidelines. A total of 95 quantitative studies examining the relationship between education level and diabetes self-management in adult T2DM patients were included. Studies were sourced from Indonesian healthcare settings including hospitals, primary care centers (Puskesmas), and community settings. Data were extracted regarding study characteristics, participant demographics, education measurement, self-management assessment, statistical associations, and moderating factors. Results: The majority of studies (approximately 65%) reported statistically significant positive associations between higher education and better self-management (r range: 0.263-0.739; p<0.05), particularly for medication adherence and dietary compliance. However, approximately 30% of studies found no significant association. Diabetes-specific knowledge, health literacy, self-efficacy, and family support consistently emerged as stronger direct predictors and significant mediators of the education-self-management relationship. Socioeconomic factors (income, employment) and healthcare access variables (Prolanis participation, health worker support) significantly modified this relationship. Discussion: The education-self-management relationship is indirect and context-dependent, primarily operating through modifiable cognitive and psychosocial mechanisms. Educational attainment serves as an enabling rather than deterministic factor. Conclusion: Interventions should target diabetes-specific knowledge, health literacy, self-efficacy, and family support systems, particularly for patients with lower formal education. Future research requires longitudinal designs, standardized measurement tools, and diverse populations beyond Indonesia.